Engineered tribological composites the art of friction material development - Cox, Roy L. (Society of Automotive Engineers, 2012)
Readers will gain a solid background about tribology, as well as a solid understanding of matrices, fibers and additives that make up engineered tribological composites. They will learn how manufacturing affects these composites, along with how friction and wear affect those materials. They will gain a better understanding of which materials provide the optimum balance of cost, friction and wear for various applications, enabling them to better create and apply engineered tribological composites for whatever application is at hand.
Title from PDF title page (SAE Web site, 08/15/2012).
Keywords: Composite materials.; Friction materials.; Automobiles -- Materials.; elektronické knihy; electronic books